Asuhan Keperawatan Pada Pasien Dengan Fraktur Femur Post Op Diruang Trauma Center RSUP Dr. M. Djamil Padang - Govin Yoganda; Debby Silvia Dewi; Mike Asmaria; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to the World Health Organization (WHO) in 2023, fracture cases worldwide have increased, with an estimated 13 million cases and a prevalence of 2.7%. In Indonesia, the prevalence of fractures reached 5.5%. Data from West Sumatra Province in 2021 recorded 128 cases of femoral fractures, while medical records from Dr. M. Djamil General Hospital Padang reported 283 femoral fracture cases in 2026. This case study aimed to provide nursing care for a patient with a femoral fracture.The study used a case study approach in medical-surgical nursing through interviews, observations, and direct nursing assessments. It was conducted in the Trauma Center of Dr. M. Djamil General Hospital Padang from March 10–15, 2026, involving one patient, Mrs. N. The results identified three nursing problems: acute pain, risk of infection, and impaired physical mobility. Nursing interventions included pain management and wound care. Evaluation showed that these problems were partially resolved by the fourth day of treatment